Effect of MgO on the structure of SiO2‐poor/rich MgO‐CaO‐SiO2 melts by in situ high temperature time‐gated Raman spectroscopy and theoretical calculation. (11th August 2022) - Gong, Xiaoye; Wang, Jian; You, Jinglin; Wang, Min; Zhang, Fu; Tang, Xiaohui; Ma, Nan; Lu, Liming; Wan, Songming; Zhang, Qingli
Abstract: The effect of MgO on the microstructures and macroscopic properties of SiO2 ‐poor/rich MgO‐CaO‐SiO2 melts was investigated by in situ high temperature time‐gated Raman spectroscopy coupled with aerodynamic levitation heating of molten samples. Results of density functional theory calculations of Mg2 SiO4, γ ‐Ca2 SiO4, and MgCaSiO4 crystals and quantum chemistry ab initio simulations of Q 0 species ( Q 0 refers to tetrahedral Si‐O units without bridging oxygen) of SiO2 ‐poor series MgO‐CaO‐SiO2 molten samples certified that with the substitution of CaO by MgO, the variation of Raman intensity at 900–1100 cm −1 of x MgO‐(2‐ x )CaO‐SiO2 melts was caused by the antisymmetric stretching vibration modes of distorted silicon‐oxygen tetrahedra. The experimental result of SiO2 ‐rich series of MgO‐CaO‐SiO2 molten samples could identify various Q i species quantitatively and demonstrated that with the substitution of CaO by MgO, the abundance of Q 3 species dramatically decreased, but Q 4 species increased slightly, whereas Q 1 and Q 2 species maintain insignificant change. A positive correlation between viscosity and the abundance ratio of Q 3 to Q 4 was assumed and illustrated. Abstract : Raman spectra of x MgO‐(2‐ x )CaO‐SiO2 and x MgO‐(0.5‐ x )CaO‐SiO2 melts were obtained by time‐gated Raman spectrometer coupling with aerodynamic levitation heating. Results showed Raman bands around 900–1100 cm −1 of x MgO‐(2‐ x )CaO‐SiO2 melts should be assigned to the antisymmetric stretching vibration modes of Q 0 species rather than symmetric stretching vibration modes of other Q i species. Quantitative analysis of Raman spectra of x MgO‐(0.5‐ x )CaO‐SiO2 melts demonstrated the substitution of CaO by MgO caused the following reaction Q 3 → Q 1 + Q 2 + Q 4 .